Food Systems Approach: Food Losses & Waste by the Dutch Ministry of Agriculture - CGIAR Research Program on Climate Change, Agriculture and Food Security (2021)
After our high level presentations to the Dutch ministry on the relation between FLW and GHGe's beginning of 2021 LNV identified the need to link FLW and GHGe's https://www.wur.nl/nl/onderzoek-resultaten/onderzoeksprojecten-lnv/expertisegebieden/kennisonline/food-systems-approach-food-losses-waste.htm